The relationship between walking speed and changes in cardiovascular risk factors during a 12-day walking tour to Santiago de Compostela: a cohort study. Issue 3 (11th May 2012) - Bemelmans, Remy H H; Blommaert, Paulus P; Wassink, Annemarie M J; Coll, Blai; Spiering, Wilko; van der Graaf, Yolanda; Visseren, Frank L J
Abstract : Objectives: Physical exercise has beneficial effects on cardiovascular risk factors. Knowledge about the effect of exercise intensity, specifically walking speed, on cardiovascular risk factors is limited. We report the relationship between walking speed and changes in cardiovascular risk factors in participants of a 12-day walking tour to Santiago de Compostela. Design: Prospective cohort study. Setting: Single-centre study with healthy middle-aged volunteers. Participants: Healthy middle-aged men (n=15) and women (n=14). Subjects using lipid-lowering medication were excluded. Intervention: Participants walked 281±10 km of the classical route to Santiago de Compostela in 12 days in 2009. Primary and secondary outcome measures: Walking speed was recorded and blood pressure, weight, waist circumference, lipids and glucose were measured every other day. Changes in risk factors were compared between gender-pooled groups with faster and slower walking speed. Second, the relationship between walking speed and changes in risk factors was quantified using a linear mixed effects model. Results: In the faster walking speed (4.6±0.2 km/h) group, high-density lipoprotein cholesterol (HDL-c) increased more than in the slower walking speed (4.1±0.2 km/h) group (difference in change between groups: 0.20; 95% CI −0.02 to 0.42 mmol/l), while low-density lipoprotein cholesterol (LDL-c) and total cholesterol decreased more in the slower walking speed group (differences in changes between groups: LDL-c: −0.50; 95% CI −0.88 to −0.12 mmol/l and total cholesterol: −0.75; 95% CI −1.19 to −0.31 mmol/l). A 1 km/h higher walking speed was related to an increase in HDL-c (0.24; 95% CI 0.12 to 0.30 mmol/l), LDL-c (0.18; 95% CI −0.16 to 0.42 mmol/l) and total cholesterol (0.36; 95% CI 0.12 to 0.60 mmol/l), adjusted for age, gender, smoking, body mass index and heart rate, during the whole walking tour. Conclusions: Walking the same distance faster improves HDL-c more, while LDL-c and total cholesterol decrease more with lower walking speed independent of changes in body weight in healthy middle-aged subjects.